Free, Prior, and Informed Consent Principles as Indigenous Peoples’ Right: Soft Law or Hard Law? - Kusniati, Retno (Faculty of Law, Jambi University, 2024)
Ensuring conformity between national laws and international law principles is crucial for states, particularly concerning the adoption of the Free, Prior, and Informed Consent (FPIC) principle to safeguard the natural resource rights of Indigenous Peoples. Numerous development initiatives proceed without indigenous consent, resulting in significant harm. Policies impacting indigenous communities should be established through prior consultation and their explicit endorsement to align with local wisdom and values. This paper explores the imperative to reevaluate the FPIC principle within legal frameworks. Using both conceptual and statutory analyses, it assesses whether FPIC constitutes a binding obligation with legal ramifications that necessitate incorporation into national law (hard law) or remains a non-binding guideline (soft law). The State’s role in implementing this principle to shield indigenous groups from detrimental development projects affecting their natural resources and cultures is scrutinized. The foundational ethos of FPIC is rooted in defending Indigenous Peoples’ entitlements to natural resources. Lastly, legislative recommendations are offered to define FPIC as a legal norm, ensuring legal certainty and guiding judicial decisions in upholding these rights